Upadek Artura J.R.R. Tolkiena w kontekście formulicznej tradycji średnioangielskiej arturiańskiej poezji aliteracyjnej - Błaszkiewicz, Bartłomiej (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The article discusses the unfinished alliterative poem by J.R.R. Tolkien entitled The Fall of Arthur in the context of the Middle-English aliterative verse tradition. Tolkien’s poem is here specifically compared to the alliterative Morte Arthure, which constitutes the most compatible example of the literary Arthurian tradition in the English High-Medieval period. The argument concentrates on such aspects of poetic composition as the use of oral-descended parallel syntactic and lexical structures as well as the question of high and low poetic register. As a result of the conducted analysis it becomes possible to account for the emerging contrast between the systematic use of the formulaic material in the medieval poem and the practice of ornamental stylisation adopted in The Fall of Arthur, which reflects the literate cultural context of its composition.
Keywords: Tolkien; Artur; aliteracja; oralność; formulaiczność